HUBUNGAN PERAN PERAWAT (EDUCATOR) DENGAN KEPATUHAN MENGKONSUMSI OBAT ANTI HIPERTENSI DAN PERILAKU PENCEGAHAN STROKE PADA PASIEN HIPERTENSI DI UPT PUSKESMAS SUNGAI PAKNING - Nanda Wilda Lestari; Imron Rosyadi (Ensiklopedia of Journal, 2023)
Adherence to taking hypertensive patients' medications and stroke prevention behaviors in hypertensive patients still do not meet the target. This is one of the phenomena for nurses to continue to strive to improve their knowledge and education so that the treatment of hypertension can be more optimal. The purpose of this study was to determine the relationship between the role of nurses (educators) and adherence to taking antihypertensive drugs and stroke prevention behaviors in hypertensive patients in the Siak Health Center Work Area. The design of this study is descriptive correlation with a cross sectional approach. This research was conducted in the Siak Puskesmas Working Area with a population of 147 people. The sampling technique is to use a total sampling of 147 people with inclusion criteria: hypertensive patients who were given an antihypertensive regimen and did not experience complications of other comorbidities. The data collection tool in this study used a questionnaire and the results of the study were processed using the Chi-square test. The results in this study found that there was a significant relationship between the role of educator nurses and adherence to taking antihypertensive drugs (p-value = 0.000) and there was a significant relationship between the role of educational nurses and the stroke prevention behavior of hypertensive patients (p-value = 0.000). The suggestion from this study is that the puskesmas can provide or make a schedule for providing counseling every week on how to take antihypertensive drugs and behaviors that prevent stroke in hypertensive patients.Keywords: Educator, Medication Adherence, Stroke Prevention